Plots on the history of ancient Oirat-Turkic communities in the text of “The Secret History of the Mongols” in the russian translation by S.A. Kozin - B. G. Ayagan (Nomadic Civilization: Historical Research, 2024)
In this article, the author presents his research into the history of ancient Oirat-Turkic communities, analysis of toponyms and basic concepts found in the text of “THE SECRET HISTORY OF THE MONGOLS” translated by S.A. Kozin, completed in 1941. The new perception of the text of the monument is due to the fact that , according to the author, for completely objective reasons, the study of S.A. Kozin could have been influenced by the policies of the Stalinist leadership, which actively interfered with the scientific activities of scientists and set political guidelines in historical science. The unceremonious interference of party bodies in science led to the distortion of scientific truth; it impeded the study of the social system of the state created by Genghis Khan. The author of the article emphasizes that the history of Genghis Khan’s empire is still not only extremely insufficiently studied, but is also considered in the limited space of translations published in the 18th-20th centuries. during the Stalinist period, when ideological censorship dominated scientists. In line with the above, the author aims to give his analysis of the Russian-language text of “THE SECRET HISTORY OF THE MONGOLS” published in 1941, and also compares and uses translations of Kazakh authors from Mongolia and the achievements of historical science in recent years. At the same time, the author of the article notes the enormous work and brilliant translation of S.A. Kozin